Debasish Lahiri’s Transgressive Ontologies (London Journal of Research In Humanities and Social Sciences, 2024)
NA
Keywords: Social rapports; deflation and inflation; constant & coordinated development; Adolescence; Developmental Task; Identity; Parenting function; Parentification.; Literature-in-English; Debasish Lahiri; Concept Poetry; Postcolonial Intersectionalities